Strategi Pengembangan Pembelajaran dan Pengajaran Bahasa Berbasis Higher Order Thinking di Era Revolusi Industri 4.0 - Lia Khairun Nisa (Indonesian Journal of Applied Linguistics Review, 2022)
Thinking skill is complex ability. Higher-order thinking skills need to be improved by keeping up with the times, especially in the industrial era 4.0. The use of diverse and interesting applications is the choice of learning and teaching development media. Educators as student companions can produce quality students in high-level thinking and can collaborate in the industrial era 4.0. The purpose of this study is to describe how strategies in developing language learning and teaching based on higher-order thinking are in accordance with today's developments. The method in this study uses a literature review design. The type of approach used in this research is a descriptive qualitative approach. The results of this study in the form of higher-order thinking skills are closely related to thinking skills in accordance with the domains of (1) cognitive, (2) effective, and (3) psychomotor.